Production of the 3pin-plug using vacuum casting / Abdul Rahim Alias and Ahmad Hazwan Ahmad Azhar - Alias, Abdul Rahim; Ahmad Azhar, Ahmad Hazwan (2005)
This project in title PRODUCTION OF THE 3 PIN-PLUG USING THE VACUUM CASTING concerns with the machine of the vacuum casting and to produced the product of the 3 pin- plug. When talking about vacuum casting, we should know the function of the machine and how to run its. We also have to learn about the process of the vacuum casting, making the silicone mold, resin and the steps of the process must completely follow the rule. The result of our mold is not the same as the 3 pin plug pattern although we follow the procedure. It might be the problem of the machine and the expired of the resin and silicone.